PENERAPAN PENDEKATAN CONTEXTUAL TEACHING AND LEARNING (CTL) UNTUK MENINGKATKAN KETERAMPILAN MEMBUAT MOZAIK SISWA KELAS IV SD NEGERI 177 PEKANBARU - Maharani Surahmi; Zariul Antosa; Lazim N Lazim N (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
AbstractThe problem in this study is the lack of skills of the students in making a mosaic . Learning this art school focused on free drawing activities only, while in the art of learning the art are attached ( mosaic ) . Based on the above issues researchers want to make improvements to the learning process approach to improve the skills of mosaic CTL fourth grade students at SDN 177 Pekanbaru FY 2013/2014 . Subjects in this study is 37 students . This research was conducted in the form of Classroom Action Research ( CAR ) with 3 cycles . Each cycle consists of 2 meetings and 1 daily test . Data collection instruments were used , namely , student activity sheets and teacher observation , rubric assessment process and results . At baseline test score average was 46.3 students make mosaics with enough categories . In the first cycle increased by 26.3 to 72.6 terampil.Lalu category on the second cycle also increased by 10.3 to 82.9 with the skilled category . Then on the second cycle increased by 1.1 to 84 with a highly skilled categories . It can be concluded that this hypothesis " If implemented Contextul Teaching and Learning approach can improve the skills of fourth grade students create mosaic SDN 177 Pekanbaru " acceptable.Keyword : Contextual Teaching and Learning (CTL), mozaic